A model proposal for ERP system selection in automotive industry - Beskese, Ahmet; Corum, Adnan; Anolay, Melis (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
ERP turned out to be one of the most valuable tools since it is a strong means to integrate the functions both within a company and among the companies within a supply chain. This study aims to propose a comprehensive model to evaluate alternative ERP packages and select the best one. The hierarchical model proposed in this study is applicable in any industry with minor modifications. However, considering the importance of automotive industry both for global and national economies, harsh competition, and many industry specific requirements, a dedicated full model is proposed. This industry specific nature together with the comprehensive model constitutes the major originality of the study. Fuzzy AHP is used to calculate the weights of criteria and sub-criteria within the model. Then, to illustrate the application of the model, fuzzy TOPSIS is utilized in a numerical example for ranking three alternative ERP systems.